Gender socioeconomic inequalities in intimate relationships : introducing the GSEI index - Klasnić, Ksenija, sociologinja (Array, 2020)
Inspired by the materialist feminist theoretical approach, this study starts from an underlying assumption that research of gender socioeconomic inequalities in intimate relationships requires the analysis of specific variables that constitute the socioeconomic status of intimate partners. Based on five indicators relevant for contemporary Croatian society, the GSEI index was constructed and applied to a representative sample of Croatian women in intimate relationships. The results showed significant gender socioeconomic inequalities between intimate partners, mostly in favour of men. The highest level of inequality between intimate partners was discovered with regard to real-estate ownership, whereas the highest level of equality between partners was found in their level of education. Although socioeconomic inequalities between intimate partners in favour of men prevail regardless of the geographic and social context, they are more pronounced in regions with more traditional values, among couples who live in rural areas, and among those who are married (in comparison with those who live in domestic partnership). A recommendation for further research and GSEI index application is to consider which are the relevant indicators for measuring gender socioeconomic inequalities in intimate relationships depending on the wider social context.